Next generation biodegradable ureteral stent in a yucatan pig model - Chew, Ben H.; Lange, Dirk; Paterson, Ryan F.; Hendlin, Kari; Monga, Manoj; Clinkscales, Kenneth W.; Shalaby, Shalaby W.; Hadaschik, Boris (The journal of urology, 2010)
PURPOSE: Ureteral stents are commonly used to facilitate kidney drainage but they may produce significant stent symptoms and morbidity, and require a secondary procedure for removal. Previous biodegradable stents showed bio-incompatibility or inconsistent degradation, requiring extra procedures to remove undegraded stent fragments. We previously reported a first generation biodegradable stent composed of suture-like material that required placement through the lumen of a sheath and degraded by 10 weeks. We now report second and third generation biodegradable stents that degrade more rapidly and can be placed directly over a polytetrafluoroethylene guidewire. - MATERIALS AND METHODS: Two groups of 16 Yucatan pigs each were unilaterally stented endoscopically with a control nondegradable (biostable) stent or a second generation degradable Uriprene stent. Blood studies, renal ultrasound and excretory urography were done throughout the study to determine renal function, hydronephrosis and stent degradation. Genitourinary organs were harvested at necropsy for pathological analysis. A third generation stent designed to improve degradation time was bilaterally implanted endoscopically into 4 Yorkshire Farm pigs (total of 8 stents), followed by excretory urography weekly to assess degradation and kidney function. Biomaterial parameters were tested. - RESULTS: Second generation stents began degrading at 2 weeks and were completely degraded by 10 weeks. All third generation stents were degraded by 4 weeks. Hydronephrosis was considerably less in the Uriprene group than in control biostable stented kidneys. Biostable stented ureters showed an average higher degree of inflammation, uropathy and nephropathy. Physical characteristics indicate that Uriprene stents are significantly more resistant to stent compression and have markedly higher tensile strength and coil strength comparable to that of other commercially available plastic stents. - CONCLUSIONS: Our study confirms that Uriprene stents are biocompatible and provide good renal drainage. They hold promise for decreasing the need for a secondary procedure and stent related morbidity, such as infection and irritative symptoms.